E-047 Vessel wall imaging and brain arteriovenous malformations: initial description of enhancement patterns. (22nd July 2019) - Garzelli, L; Boulouis, G; Blauwblomme, T; Levy, R; Boddaert, N; Ben Hassen, W; Trystram, D; Rodriguez, C; Dangouloff-Ross, V; Nataf, F; Oppenheim, C; Brunelle, F; et al.
Abstract : Purpose: Usefulness of Intracranial Vessel Wall Imaging (VWI) on 3 Tesla Magnetic Resonance Imaging (3T MRI) performed on Postcontrast 3D Turbo Spin-Echo MR Imaging Sequence (CUBE, GE Healthcare, Chicago, United-States) has been demonstrated in the management of intra-cranial aneurysm. Our purpose was to describe patterns and prevalence of wall enhancement in brain arterio-venous malformations (bAVM). Methods: Pediatric and adult patients diagnosed with bAVM and referred respectively to a pediatric quaternary care center between 2016 and 2018 and to a tertiary care center between 2013 and 2018 who underwent at least one CUBE sequence (initially or during follow-up) were pooled and retrospectively analyzed. Baseline clinical, demographic and imaging data were retrospectively analyzed. Imaging were reviewed for key bAVMs angioarchitectural characteristics, i.e, nidus size, location, Spetzler Grade, venous drainage, arterial or nidal aneurysm and the presence of vessel wall enhancement (nidal, venous or arterial). Chi-squared test was used with a threshold of p<0.05 to be considered significant. Results: 52 patients, 19 children and 33 adults (mean age: 31 y.o; median: 43 y.o) with 52 bAVM were included. 47% patients were untreated when the first CUBE was performed. 21 bAVM were ruptured, more frequently in children (12/19 versus 9/33; p=0.01). Parietal wall enhancement was observed in 16/21 ruptured bAVM and 27/31 unruptured bAVM. In ruptured bAVM, the site of the rupture, either venous ectasia or nidal aneurysm, demonstrated a wall enhancement in 30% of cases. In unruptured bAVM, enhancement rate did not differ between children and adults (6/7 versus 21/24). Conclusion: The prevalence of wall enhancement in bAVM vascular constituent is high, in both ruptured and unruptured lesions and was similar in adult and pediatric population. Further studies are warranted to determine the potential role of VWI in bAVM. Disclosures: L. Garzelli: None. G. Boulouis: None. T. Blauwblomme: None. R. Levy: None. N. Boddaert: None. W. Ben Hassen: None. D. Trystram: None. C. Rodriguez: None. V. Dangouloff-Ross: None. F. Nataf: None. C. Oppenheim: None. F. Brunelle: None. M. Edjlali-Goujon: None. O. Naggara: None.